Multistep optimization for the electrodeposited mixed perovskite FA 1−y Cs y PbBr x I 3−x solar cells - Xiang, Yanhong; Zheng, Ren; Li, Chunhe; Ren, Kuankuan; Ye, Qiufeng; Shi, Biyun; Liu, Shiyan; Fang, Zebo (Nanotechnology, 2024)
The electrodeposition method has recently been developed for the fabrication of perovskite solar cells due to its potential advantages in commercial preparation. However, there is few studies on the preparation of perovskite solar cells by the electrodeposition method, especially on the perovskite FAPbI 3 -based solar cells. Herein, we fabricated the mixed perovskite FA 1− y Cs y PbBr x I 3− x solar cells by an optimized electrodeposition method, in which the electrodeposited PbO 2 reacts directly with FAI and an appropriate amount of CsBr dopants. The corresponding solar cells display the best PCE of 4.97%. By regulating the growth temperature in the reaction between PbO 2 and FAI/CsBr, the efficiency of the mixed perovskite solar cells can be promoted to 10.18%. These results illustrate that the element doping and growth environment regulation can optimize the quality of the perovskite films, thus promoting the efficiency of the perovskite solar cells. With further optimizing the growth process in the electrodeposition method, it is expected to open up a new commercial preparation route for the perovskite solar cells in the near future.